2001
DOI: 10.1186/gb-2001-2-10-research0041
|View full text |Cite
|
Sign up to set email alerts
|

Genomic-scale measurement of mRNA turnover and the mechanisms of action of the anti-cancer drug flavopiridol

Abstract: Background: Flavopiridol, a flavonoid currently in cancer clinical trials, inhibits cyclin-dependent kinases (CDKs) by competitively blocking their ATP-binding pocket. However, the mechanism of action of flavopiridol as an anti-cancer agent has not been fully elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(91 citation statements)
references
References 42 publications
(51 reference statements)
3
86
1
Order By: Relevance
“…On the other hand, these anti-apoptotic proteins are dependent on continuous RNAPII activity mediated by overexpression of CDK9. CDK9 inhibition using small-molecule inhibitors (Table 3) downregulates these short-lived anti-apoptotic proteins and triggers cell death (Lam et al 2001, Chen et al 2009). In 2014, Booher et al showed that CDK9 inhibitor dinaciclib induces apoptosis by downregulating MCL-1 and BCL-XL in 22rv1 and PC3 PCa cells, as well as other 11 solid tumor cells.…”
Section: Targeting Cdk9 In Crpcmentioning
confidence: 99%
“…On the other hand, these anti-apoptotic proteins are dependent on continuous RNAPII activity mediated by overexpression of CDK9. CDK9 inhibition using small-molecule inhibitors (Table 3) downregulates these short-lived anti-apoptotic proteins and triggers cell death (Lam et al 2001, Chen et al 2009). In 2014, Booher et al showed that CDK9 inhibitor dinaciclib induces apoptosis by downregulating MCL-1 and BCL-XL in 22rv1 and PC3 PCa cells, as well as other 11 solid tumor cells.…”
Section: Targeting Cdk9 In Crpcmentioning
confidence: 99%
“…10-15). However, there has been only limited application of DNA microarrays to the study of kinetic events such as mRNA decay (16)(17)(18).…”
mentioning
confidence: 99%
“…5 shows that both cellular protein and mRNA levels of Mcl-1, XIAP, and survivin are down-regulated by ibulocydine in a time-dependent manner in HCC cells. It has been suggested that prolonged inhibition of Cdk7 and Cdk9 within cells induces apoptosis (35). The prolonged inhibition of Cdk7 and Cdk9 eventually affected all transcripts produced by RNA polymerase II, and subsequently their proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged inhibition of Cdk7 and Cdk9 eventually affected all transcripts produced by RNA polymerase II, and subsequently their proteins. This has an immediate effect upon transcripts and proteins with inherently rapid turnover rates (35), such as Mcl-1, XIAP, survivin, etc. Thus, studies have speculated that prolonged Cdk7/9-mediated inhibition of transcription decreases Mcl-1, XIAP, and survivin expression, releasing their ability to block primed cells from undergoing apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%